Sistem pakar deteksi dini kesehatan mental mahasiswa dengan metode Forward Chaining - Alvi Zumaela Izdiana; Tikaridha Hardiani (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2026)
Mental health is a crucial aspect that significantly influences individuals' daily lives. Data from the 2023 mental health screening conducted by the Psychology Service Bureau (BLP) of Universitas 'Aisyiyah Yogyakarta showed that 16.8 percent of students experienced indications of mental health disorders out of a total of 857 participants. The screening process was conducted using Google Forms. However, this method has several limitations, particularly the inability to directly assess mental health status or provide immediate feedback to participants after completing the screening. Students may not receive timely information regarding their mental condition or recommendations for further action. This study aims to develop a web-based expert system that uses the Forward-Chaining method to determine a person's mental condition. The system is developed using Expert System Development Life Cycle (ESDLC), which includes knowledge acquisition, system design, implementation, and testing stages. After functional and accuracy testing, the results indicate that the system is ready for use, achieving 100 percent accuracy in detecting indicators of mental health issues among college students.